(untitled) (Nexo Revista Científica, 2019)
One of cases considered for diagnosing DNA damages is diagnosing DNA probable damages against oxidizing agents, including oxidizing chemicals and various incident rays which cause the bases in the DNA to be oxidized and especially bases G in the DNA sequence which is more easily oxidized than the other bases. Therefore, the main objective of this comprehensive survey is to provide relevant information on measure physical chemical properties of nucleic acids during DNA radicalization and incidence of cancer using theoretical methods. The aim of the present study is to examine the single-stranded NBO with sequences of GG, CG, AA AG AC: AT CT GT TT followed by the levels of energy and form of orbital LUMO and HOMO obtained from Gaussian computations for above double-stranded sequences. Our results showed that form B genetic material is the most stable structure against physical and chemical agents. Only the number of molecular population and the levels of molecular dynamic vibration and molecular thermochemistry such as enthalpie and entropie are temperature independent. In addition to this, the gap between the layers and the potential and energy needed to oxidize the components in the two strands of DNA and its optimum structure will not change with temperature. Optimum conditions on DNA and its bonds are the temperature of 37 ° C and pH is 7 to 8.7. DNA has form B and the rate of physical protection is the highest.